2012
DOI: 10.1093/cercor/bhr379
|View full text |Cite
|
Sign up to set email alerts
|

Content Representation in the Human Medial Temporal Lobe

Abstract: Current theories of medial temporal lobe (MTL) function focus on event content as an important organizational principle that differentiates MTL subregions. Perirhinal and parahippocampal cortices may play content-specific roles in memory, whereas hippocampal processing is alternately hypothesized to be content specific or content general. Despite anatomical evidence for content-specific MTL pathways, empirical data for content-based MTL subregional dissociations are mixed. Here, we combined functional magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
110
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 90 publications
(144 reference statements)
17
110
1
Order By: Relevance
“…Furthermore, future work can address what aspects of an experience modulate postencoding persistence. In the current study, distinct features of the encoding experience, including bottom-up sensory differences in the stimulus content and top-down processes (reflecting different instructions and decisions across the tasks) (35)(36)(37), could have contributed to the distinctive hippocampal patterns seen during OF and SF encoding.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, future work can address what aspects of an experience modulate postencoding persistence. In the current study, distinct features of the encoding experience, including bottom-up sensory differences in the stimulus content and top-down processes (reflecting different instructions and decisions across the tasks) (35)(36)(37), could have contributed to the distinctive hippocampal patterns seen during OF and SF encoding.…”
Section: Discussionmentioning
confidence: 75%
“…Functional neuroimaging studies have likewise found group‐level HC activation during scene discrimination [Aly et al, 2013; Lee et al, 2008], scene construction/imagining [Zeidman et al, 2015], and working memory [Lee and Rudebeck, 2010b; Park et al, 2003]. Studies applying multivariate analysis techniques have also found evidence that the HC contains activation patterns that are sensitive to scene‐related information [Bonnici et al, 2012; Liang et al, 2013; but see Diana et al, 2008]. Overall, these extant data, when viewed alongside the large‐scale analysis of individual‐level data reported here, suggest that the HC should be considered a key region in the putative scene processing network [see also Kornblith et al, 2013; Kreiman et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…The perirhinal cortex has been associated with object perception (Buckley & Gaffan, 2006;Devlin & Price, 2007), and dissociations between perirhinal and parahippocampal cortices are found for object and scene stimuli, respectively (Litman et al, 2009;Staresina et al, 2011). Whereas the anterior hippocampus and subiculum responses seem content general, the posterior hippocampus discriminates scenes better than other stimuli (Liang et al, 2013;Preston et al, 2010). The anterior MTL is also found to be more selective to faces compared to the posterior MTL (Liang et al, 2013), and the amygdala has been linked with face recognition (Kleinhans et al, 2007;Young et al, 1995).…”
Section: Applications Of Memorability To Neuroscience Studymentioning
confidence: 99%
“…Whereas the anterior hippocampus and subiculum responses seem content general, the posterior hippocampus discriminates scenes better than other stimuli (Liang et al, 2013;Preston et al, 2010). The anterior MTL is also found to be more selective to faces compared to the posterior MTL (Liang et al, 2013), and the amygdala has been linked with face recognition (Kleinhans et al, 2007;Young et al, 1995). However, these regions are incredibly difficult to image, and only recently has work in this field begun incorporating muitivariate techniques.…”
Section: Applications Of Memorability To Neuroscience Studymentioning
confidence: 99%